Idosos com alterações cognitivas: estudando o apoio social em diferentes contextos de vulnerabilidade social - Brito, Tábatta Renata Pereira de (Universidade Federal de São Carlos, 2010)
Social support can promote better health, helping to keep the elderly independent in their familiar and social-cultural context, which is essential for cognitive function and psychological well-being. This study aimed to investigate the association between social support of elderly people with cognitive impairments and the different contexts of social vulnerability that are exposed in the municipality of São Carlos. This is a descriptive transversal study of quantitative character. The subjects were 85 elderly residents in different areas of social vulnerability, that they had presented results in the Exam Mini of Mental State below the cutoff. All ethical guidelines were observed. It were applied the Brazil Criteria, Exam Mini of Mental State (EMMS), Medical Outcomes Study (MOS), Diagram of Choice , Katz Index and the Functional Activities Questionnaire of Pfeffer. There has been a descriptive analysis and correlation of data through statistical tests. The results show that among women, most living in the context of very low, low and middle social vulnerability. Among men, the majority were residents of regions of high and very high social vulnerability. In both contexts there were mostly elderly people aged 70 to 79 years, and reported that they were white, Catholic, and monthly income of up to one minimum wage. In regions of high and very high vulnerability were greater numbers of elderly illiterate, while in the context of very low, low and medium vulnerability dominance of older people with schooling 1-3 years. The performance of the elderly in basic and instrumental activities of daily living revealed that among the independent elderly, the majority resides in the context of high and very high social vulnerability. Among dependents, the majority are resident in regions with very low, low and medium vulnerability. Social support was measured by the frequency that the elderly have different types of support. In regions of high and very high social vulnerability, the levels of social support in the dimensions of material support, emotional, informational and positive social interaction are better when compared with the context of very low, low and medium vulnerability. There were significant correlations between the dimensions of support and the IPVS variables, family income, number of people living in the household, presence of children in the home for the elderly, and the results of the Pfeffer's Questionnaire. Regarding social support network of elderly people with cognitive impairment, residing in the context of high and very high social vulnerability, the results showed that in this context the elderly have a great social network, with a predominance of members of his inner circle, and that also they provide more support than they receive. Data analysis can help identify the profile of the elderly vulnerable, encouraging proper structuring of health actions and assisting in the implementation of health attention policy for the elderly.
Keywords: Enfermagem; Saúde do idoso; Transtornos cognitivos; Vulnerabilidade social; Apoio social; Idoso; Nursing; Aged; Cognition disorders; Social vulnerability; Social support; CIENCIAS DA SAUDE::ENFERMAGEM